Fundo Nacional do Idoso e as políticas de gestão do envelhecimento da população brasileira - Rozendo, Adriano da Silva; Justo, José Sterza [UNESP] (My University, 2012)
Demographic census from the last decades of the twentieth century began to reveal a tendency concerning the increasing average age of the population. The Brazilian government began introducing ways to manage the effects and consequences of this trend, the most recent being the creation of the "Fundos do Idoso" (Funds for seniors) in the Federal, state and municipal spheres. That law allows transferring federal taxes from common citizens and companies to the funds. This article is specifically written as a critical examination of this governmental initiative towards the problem of an ageing population from the point of view as to how the law has been implemented. With the creation of the funds there will be the enlargement and improvement of services destined for seniors. However, the law mentioned above does not predict an active participation of the seniors in the management of this funds and policies that will come as result.

La investigación demográfica de las décadas pasadas del siglo XX había comenzado a divulgar una tendencia de la población brasileña: el crecimiento del cociente de los más viejos. Desde entonces, los gobiernos habían tenido eso para movilizar esfuerzos de manejar las consecuencias diversas de tal fenómeno, siendo la iniciativa más reciente la creación, "os Fundos do Idoso" (Fondos de mayores). Tal ley autoriza la transferencia de impuestos de la gente y de compañías a los Fondos. El actual artículo si dedica a la examinación crítica de esta iniciativa del gobierno en la gerencia del envejecimento, conduciendo en la consideración el contexto en el cual la ley será puesta en ejecución. Es posible prever, como efecto posible, la mejora de los servicios destinados a los envejecidos, sin embargo, la ley mencionada no predice que una participación activa de los mayores en la dirección de este financia y políticas que vendrán como resultado.

Os censos demográficos das últimas décadas do século XX começaram a revelar uma tendência da população brasileira: o crescimento da proporção dos mais velhos. Desde então, os governos tiveram que mobilizar esforços para gerir as conseqüências diversas de tal fenômeno, sendo a mais recente iniciativa a criação, mediante lei, dos Fundos Municipal, Estadual e Nacional do Idoso. Tal lei autoriza o repasse de imposto devido por pessoas físicas e jurídicas aos Fundos. O presente artigo se dedica ao exame crítico dessa iniciativa de governo na gestão do envelhecimento, levando em consideração o contexto no qual a Lei vem sendo implementada. Com a criação do fundo haverá a ampliação e melhoria dos serviços destinados aos idosos, porém, a referida lei não prevê uma participação ativa dos próprios idosos na gestão deste fundo e políticas que dele decorram.
Fundo Nacional do Idodo and the management policies of the aging of Brazilian population
Fundo Nacional do Idoso y las políticas de dirección de la población brasileña envejecida
Keywords: Ageing; Population; Legislation; Funds for seniors; Management; Envejecimiento; Población; Legislación; Fundo do Idoso; Dirección; Envelhecimento; População; Legislação; Fundo do Idoso; Gestão